IMPLEMENTASI METODE AL-MIFTAH LIL ULUM SIDOGIRI DALAM PENINGKATAN KEMAMPUAN MEMBACA KITAB KUNING SANTRI MADRASAH DINIYAH KELAS I’DADIYAH (STUDI MULTISITUS DI PONDOK PESANTREN MIFTAHUL ULUM RU4 PUTRA DAN PONDOK PESANTREN MIFTAHUL ULUM RU4 PUTRI MALANG) - Islamiyah, Sinta; Busthomi, Yazidul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze the implementation of the Al-Miftah Lil Ulum Sidogiri Method in developing students’ ability to read classical Islamic texts (kitab kuning) at the I’dadiyah level of Madrasah Diniyah in Miftahul Ulum Ru4 Islamic Boarding School for male and female students in Malang. This research employed a qualitative approach using a multisite study design. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing, complemented by cross-site analysis.The findings indicate that the implementation of the Al-Miftah Lil Ulum Method was conducted through systematic stages of planning, implementation, and evaluation using a graded level (jilid) system. The method effectively enhanced students’ understanding of basic nahwu and sharaf principles and their ability to apply these rules in reading unvowelled Arabic texts in a gradual and practical manner. Cross-site analysis revealed similarities in learning objectives, material structure, and instructional stages, while differences were found in classroom management and pedagogical approaches influenced by the characteristics of male and female students. The main challenges included students’ heterogeneous initial abilities, limited instructional time, and fluctuating concentration levels. These challenges were addressed through additional learning sessions, reinforcement of grammatical memorization, and individualized guidance. This study concludes that the Al-Miftah Lil Ulum Sidogiri Method is flexible, contextual, and effective for improving students’ kitab kuning reading skills at the I’dadiyah level of Madrasah Diniyah. Keywords: Al-Miftah Lil Ulum Method, Kitab Kuning, Madrasah Diniyah, I’dadiyah Level, Multisite Study